ANALISIS LEVEL OF SERVICE (LOS) DAN OPTIMALISASI WAKTU SIKLUS PADA SIMPANG BERSINYAL PADA MIKROSIMULASI VISSIM - Rizqy Ridho Prakasa; Edi Yusuf Adiman; Dika Meilisan; Nofreta Ersyi Darfia; Randhi Saily; Intan Monica MG; Vinka Lyona; Benny Hamdi Rhoma Putra; Safridatul Audah; Soewignjo Agus Nugroho (Jurnal Infrastruktur, 2025)
Tabek Gadang signalized intersection, which links Jl. Soebrantas and Jl. SM Amin, is one of the key intersections in Pekanbaru City that frequently experiences traffic congestion. This issue arises because the intersection serves as a connector for several vital zones, including educational institutions, office areas, commercial centers, and residential neighborhoods, leading to heavy traffic buildup, particularly during rush hours. This issue, the present study proposes an optimization of the signal cycle time using VISSIM-based microsimulation modeling. Main of objective this research to evaluated intersection’s operational performance following the optimization process. The analysis conducted through VISSIM microsimulation reveals that optimizing the signal cycle time from the existing condition to 50 seconds results in a reduction of average delay from 29.6 seconds and improves level of service from category F to D.